“Nomophobia: Prevalence, associated factors, and impact on academic performance among nursing students” - Maryam Janatolmakan; Alireza Karampour; Shahab Rezaeian; Alireza Khatony (Heliyon)
Background: The literature offers limited and conflicting evidence regarding the prevalence, associated factors, and impact of nomophobia on nursing students' academic performance. Objective: This study aimed to investigate these aspects among nursing students. Method: A cross-sectional design and convenience sampling method were used to recruit 500 nursing students. Data were collected using a demographic information form and a nomophobia questionnaire. Students were categorized into two groups based on their previous semester grade point average (GPA): strong (GPA >15) and weak (GPA ≤15). Descriptive and inferential statistics, including the chi-square test and linear regression, were used for data analysis in SPSS-18 software. Results: The study found a considerable prevalence of nomophobia (approximately 80 %) among nursing students. Significant differences in nomophobia scores were observed based on gender and primary smartphone usage. However, no statistically significant difference was found in mean nomophobia scores between strong and weak students, nor was there a significant correlation between nomophobia scores and academic performance. Conclusion: This study highlights the high prevalence of nomophobia among nursing students and its potential implications for their physical and mental well-being. Although no significant association was found between nomophobia and academic performance, educating students about the potential risks of nomophobia and encouraging responsible smartphone use remains crucial. Future research should focus on developing interventions and preventive strategies to mitigate the adverse effects of nomophobia.